Peningkatan Kreativitas Anak Usia Dini melalui Metode Permainan Konstruktif: Studi Penelitian Tindakan Kelas - Soleha, Anis; Nur, Lutfi; R, Anggi Maulana (Lembaga Yasin AlSys, 2025)
Creativity is a vital 21st-century skill that must be nurtured from an early age to support critical thinking and independent idea expression. However, observations at TK Fathul Huda Tasikmalaya indicate that the creativity of children aged 4–5 years has not yet developed optimally, as evidenced by a tendency to imitate, the production of meaningless work, and a limited ability to express ideas. This study aims to enhance children’s creativity through the use of constructive play methods. The research employed a Classroom Action Research (CAR) approach in collaboration with teachers, conducted over three cycles. Creativity assessment was based on Utami Munandar’s 4P theory, encompassing the individual, process, product, and press (environment) dimensions, with indicators such as the ability to create original forms, self-motivated artistic activity, sustained creative engagement, and the production of meaningful, describable work. The results showed a significant increase in creativity across each cycle, with the majority of children reaching the